Future of Drug Discovery - Tamas Bartfai (Elsevier/Academic Press, 2013)
"The Future of Drug Discovery: Who decides which diseases to treat? provides a timely and detailed look at the efforts of the pharmaceutical industry and how they relate, or should relate, to societal needs. The authors posit that as a result of increasing risk aversion and accelerated savings in research and development, the industry is not developing drugs for increasingly prevalent diseases, such as Alzheimer's disease, untreatable pain, antibiotics and more. This book carefully exposes the gap between the medicines and therapies we need and the current business path. By analyzing the situation and discussing prospects for the next decade, the The Future of Drug Discovery is a timely book for all those who care about the development needs for drugs for disease."--Publisher's website.